Eye care service utilization and associated factors among adults in Debre Berhan Town, North Shewa, Ethiopia, 2023 - Bekele, Matiyas Mamo; Shumye, Abebech Fikade; Tegegn, Melkamu Temeselew (Frontiers in Public Health, 2024)
Introduction: Globally, the utilization of eye care services varies widely, ranging from 18% to 90%.Low utilization of eye care services can lead to delayed detection of vision problems. However, there is limited data on the proportion of eye care service utilization and its associated factors in Ethiopia at the community level.The objective of this study was to determine the proportion of eye care service utilization and its associated factors among adults in Debre Berhan town, North Shewa, Ethiopia.Methods: A community-based cross-sectional study was conducted on 960 adults in Debre Berhan town from May 8 to June 8, 2023, using a multistage sampling method. Binary logistic regressioN was performed. Variables with a P-value of less than 0.05 were considered significant.Results: A total of 940 study participants participated, resulting in a response rate of 97.9%. The mean age of the participants was 54.67 years (SD ± 8.69). The proportion of good-level eye care service utilization was found to be 32.98%(95%CI:29.97,35.99). Factors positively associated with good-level eye care service utilization included older age (AOR=1.